The Mosque as a Source of Community Prosperity: Lessons from the Jogokariyan Mosque - Hidayat, Taufik; Hudiwasono, Kodar; Rahmi, Rieny Fadhilah; Ningrum, Cahya; Basdiati, Basdiati (Journal of Islamic Economics and Philanthropy, 2024)
The research was conducted to analyze the role of programs to increase the independency and prosperity of community held by the Jogokariyan Mosque in Special Region of Yogyakarta. The research methode is qualitative method with the approach of Interactive Model Analysis was used along with the observation during the period of January, 2022 until March 2022. The study showed that Jogokariyan Mosque conducted programs in field of social, economic, health, education and covid-19 pandemic handling. In the social Jogokariyan Mosque’s have program Jogokaryan Ramadhan village, Jogokariyan Mosque’s Rice ATM, and Jogokariyan’s Public Market. In the economics Jogokariyan Mosque’s have program the development of Small Micro and Medium Enterprises (SMME), At the during the covid-19 pandemic Jogokariyan Mosque’s Special Program. Jogokariyan Mosque programs could be used as a lesson learned on how a mosque could improve its role in the community to accelerated the increase of community prosperity.